2022
DOI: 10.1111/jfpp.16667
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for detection of vanaspati ( hydrogenated fat ) in cow ghee ( clarified butter fat ) using flash gas chromatography electronic nose combined with chemometrics

Abstract: This study aimed to detect various proportions of vanaspati mixed with cow ghee using an electronic nose (e‐nose) based on fast gas chromatography. The e‐nose apparatus was equipped with a non‐polar and medium polar column used to generate two chromatograms simultaneously along with the volatile compound information. Further investigation on the adulteration detection in ghee was carried out using chemometric analysis such as principal component analysis (PCA), discriminant function analysis (DFA), and soft‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this paper [10], the authors present an IoT-based system for detecting the presence of formalin in fruits and vegetables using machine learning approaches. The study [11] demonstrated the potential of using an e-nose equipped with eight different MOS-type gas sensors, in combination with chemometrics techniques such as PCA and DFA. The goal of this study [12] was to the development of cost-effective electronic nose technology was accomplished by employing colorimetric sensors.…”
Section: Adulterationmentioning
confidence: 93%
“…In this paper [10], the authors present an IoT-based system for detecting the presence of formalin in fruits and vegetables using machine learning approaches. The study [11] demonstrated the potential of using an e-nose equipped with eight different MOS-type gas sensors, in combination with chemometrics techniques such as PCA and DFA. The goal of this study [12] was to the development of cost-effective electronic nose technology was accomplished by employing colorimetric sensors.…”
Section: Adulterationmentioning
confidence: 93%
“…Sesame oil has a distinctive fatty acid composition, characterized by the presence of specific fatty acids, such as oleic acid, linoleic acid, and palmitic acid [ 14 ]. Gas chromatography (GC) and high-performance liquid chromatography (HPLC) are widely employed to separate and identify fatty acids in oil samples [ 15 , 16 ]. By comparing the fatty acid profiles of suspected samples with known authentic sesame oil profiles, it is possible to identify adulteration or oil substitutions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Continued research and advancements in this field will contribute to more robust and reliable methods for combating fraud in the sesame oil industry, ensuring consumer trust and product integrity. However, it is important to note that while e-nose technologies show promise, there are still significant challenges because this is still an emerging field with ongoing research and development [ 16 ]. Further studies are needed to optimize e-nose sensor arrays, improve detection limits, and enhance the specificity and selectivity of the electronic nose for sesame oil fraud detection.…”
Section: Introductionmentioning
confidence: 99%